2020
DOI: 10.3390/agronomy10111829
|View full text |Cite
|
Sign up to set email alerts
|

The Colonization of Grape Bunch Trash by Microorganisms for the Biocontrol of Botrytis cinerea as Influenced by Temperature and Humidity

Abstract: Six commercial biocontrol agents (BCAs: Aureobasidium pullulans, Bacillus amyloliquefaciens, B. amyloliquefaciens plantarum, B. subtilis, Metschnikowia fructicola, or Trichoderma atroviride) were applied to bunch trash that was then incubated at one of five temperatures (T, 15, 20, 25, 30, and 35 °C) and one of five relative humidity levels (RH, 60, 80, 90, 95, and 100%). After 1 to 13 days of incubation (BCA colonization period), the number of colony forming units (CFUs) was assessed. The colonization of bunc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 61 publications
2
8
0
Order By: Relevance
“…The results of our work can then contribute to the development of a decision-making process for BCA applications, which includes the following steps: (i) assess the risk of B. cinerea infection using mathematical models ( González-Domínguez et al., 2015 ); (ii) define the BCA candidates that can be used based on the plant substrate (inflorescences, bunch trash, and berries at different ripening stages) at the time of application ( Fedele et al., 2020b ; Fedele et al., 2020c ); and (iii) define the BCA with the highest probability to be effective [i.e., the BCA whose ecological requirements best fit with the weather conditions in the days following application ( Loureiro et al., 2012 ; Fedele et al., 2020b )]. This decision-making process needs further developments and test under vineyard conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The results of our work can then contribute to the development of a decision-making process for BCA applications, which includes the following steps: (i) assess the risk of B. cinerea infection using mathematical models ( González-Domínguez et al., 2015 ); (ii) define the BCA candidates that can be used based on the plant substrate (inflorescences, bunch trash, and berries at different ripening stages) at the time of application ( Fedele et al., 2020b ; Fedele et al., 2020c ); and (iii) define the BCA with the highest probability to be effective [i.e., the BCA whose ecological requirements best fit with the weather conditions in the days following application ( Loureiro et al., 2012 ; Fedele et al., 2020b )]. This decision-making process needs further developments and test under vineyard conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The colonization of fruit wounds by antagonists and effective competition with pathogenic fungi and bacteria are also influenced by other factors, including natural non-pathogenic microorganisms at the wound, antagonist concentration, the amount of available nutrients, temperature and humidity [ [123] , [124] , [125] ]. Bencheqroun et al [ 126 ] observed that antagonist ( A. pullulans strain Ach1-1) could reduce germination percentages of P. expansum conidia at lower apple juice concentration (0–5%).…”
Section: Biocontrol Of Yeasts In Agricultural Productsmentioning
confidence: 99%
“…Over the period from flowering to pre-bunch closure (Modified Eichhorn-Lorenz growth stages 19–31), there is an abundance of senescent and necrotic floral tissues consisting of dead stamens, aborted flowers, aborted berries and calyptras [ 4 , 35 , 42 , 50 ]. Retention of these tissues in rapidly developing bunches can become problematic and B. cinerea is able to survive and effectively over-summer in a saprophytic state.…”
Section: Cultural Control Of Bbrmentioning
confidence: 99%
“…Some clones such as UCD15 Chardonnay are especially susceptible to trash retention. Not surprisingly, the relationship between B. cinerea infection of bunch trash and subsequent BBR is well established in the literature, [ 50 , 51 , 52 ]. The impact of debris retention on BBR of the Vitis interspecific hybrid Vignoles was investigated between 2001 and 2005 by Hed, Ngugi, and Travis [ 53 ].…”
Section: Cultural Control Of Bbrmentioning
confidence: 99%